المبادئ العامّة للفكر الأصول-فقهي الإسلامي في تعامله مع النّصّ: General Principles of Islamic Jurisprudence (Usul al Fiqh) in Its Handling of the Holy Text - صالح أيمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2014)
هدف هذا البحث إلى استقراء المبادئ الكلّيّة الّتي حكمت ولا تزال تحكم علم أصول الفقه الإسلامي في تعامله مع النّصّ الدينيّ، وتعيينها، وعرضها عرضاً موجزاً. هذا العلم الذي يرسم منهجيّة البحث بالنّسبة للعلوم الدّينيّة الأخرى والفكر الإسلاميّ بعامّة. وقد استطاع الباحث أن يتوصّل إلى اثني عشر مبدأً، هي تقريباً محلّ اتّفاقٍ بين الأصوليّين. وهذه المبادئ هي: 1) الاحتكام إلى النّصّ. 2) صِدْق النّصّ ومعقوليته. 3) شمول النّصّ بلفظه ومعناه للوقائع. 4) عموم النّصّ في الأشخاص إلى يوم القيامة. 5) إعْمال مَقاصد النّصّ. 6) انسجام النّصّ وتكامله. 7) عربيَّة النّصّ. 8) حمل النّصّ على ظاهِره إلا لدليل. 9) إعْمال الحال في مقال النّصّ. 10) الاحتِجاج بالنّصّ الثّابت الدّالّ الْمُحكم الرّاجح. 11) احترام تفسيرات المجتهدين للنّصّ. 12) اشتِراط أهليَّة المجتهد في النّصّ. This study aimed at deducting and briefly demonstrating the general principles that dominated and still dominating the science of Islamic Jurisprudence (Usul al Fiqh), the branch of Islamic science, which dictates the methodology of dealing with the holy Islamic text to other branches of Islamic sciences and consequently to the Islamic thought in general. The researcher managed to conclude twelve general principles, which are agreed upon by all the scholars of Islamic Jurisprudence (Usul al Fiqh) or the vast majority of them. These principles are: 1) the command of Text. 2) The Truthfulness and reasonability of the Text. 3) The comprehension of the Text to the events. 4) The comprehension of the text to the people until the judgment day. 5) The empowerment of the text aims. 6) The harmony and integration of the Text. 7) The arabisizm of the text. 8) Interpreting the text depending on the common meanings unless proven false. 9) Empowering the context of situation. 10) Using the proven true, to the point, unabrogated and superior Text in arguments. 11) Respecting the different scholars' interpretations of the text. 12) The necessity of being illegible to interpret the Text.